The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0004-282x2002000500001
|View full text |Cite
|
Sign up to set email alerts
|

Hemicrania continua: a report of ten new cases

Abstract: -Hemicrania continua (HC) is an uncommon primary headache first described as a syndrome in 1984. Being quite unusual, its clinical characterization still demands better description. The aim of this study is to present the main clinical characteristics of 10 patients with the diagnosis of HC seen in a tertiary center, critically discussing their main features. All subjects had strictly unilateral headache without side shift and absolute response to indomethacin. Seven patients (70%) presented autonomic features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Jabs and jolts like pain (stabbing headache) are important associated pains during exacerbation phase. They were noted in 20%–41% patients with HC in different case series 6,14,37. However, this prevalence matches with the normal prevalence of stabbing headache in the general population.…”
Section: Other Associated Headache Disorderssupporting
confidence: 54%
“…Jabs and jolts like pain (stabbing headache) are important associated pains during exacerbation phase. They were noted in 20%–41% patients with HC in different case series 6,14,37. However, this prevalence matches with the normal prevalence of stabbing headache in the general population.…”
Section: Other Associated Headache Disorderssupporting
confidence: 54%
“…A response to indomethacin as 'sine qua non' for making a diagnosis of HC has been debated in the past (8,(27)(28)(29), and various authors suggested a possibility of indomethacin-resistant HC (7,8). HC-like headaches unresponsive to indomethacin were three times more common than typical HC in Marmura et al's case series.…”
Section: Response To Indomethacinmentioning
confidence: 99%
“…However, incidence and prevalence of indomethacin related side effects in patients of HC in other case series were about 20-50% [7][8][9]. Beside these, other cases of indomethacin related side effects in HC are mentioned in those conditions where drugs other than indomethacin were used.…”
Section: Discussionmentioning
confidence: 99%
“…We found at least 31 patients in the literature who showed complete and persistent effects by drugs other than indomethacin-cyclooxygenase-2 inhibitors, topiramate, piroxicam, melatonin, acetyl salicilic acid, ibuprofen, verapamil, and gabapentine (Table 1). Beside this, there are many case reports where above mentioned drugs and few other drugs (such as lamotrigine, methysegide, lithium carbonate, naproxen, paracetamol with caffeine) provided significant (although incomplete and/or transient) effect on the patients of HC [2,[6][7][8][9][10][15][16][17][18][19][20][21][22][23][24][25][26]. This observation is important.…”
Section: Discussionmentioning
confidence: 99%